2015
DOI: 10.1039/c5py00273g
|View full text |Cite
|
Sign up to set email alerts
|

Triethylene glycol-based poly(1,2,3-triazolium acrylate)s with enhanced ionic conductivity

Abstract: International audienceA series of cationic poly(acrylate ionic liquid)s having a triethylene glycol (TEG) spacer and a pendant 1,2,3-triazolium group is synthesized by post-polymerization sequential chemical modifications. A chloride-functionalized polyacrylate common precursor is first obtained by reversible addition-fragmentation chain transfer (RAFT) polymerization of a TEG-based chloride-functionalized acrylate. Sequential azidation, copper-catalyzed azide-alkyne cycloaddition with 1-pentyne and alkylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 44 publications
4
39
0
Order By: Relevance
“…They confirmed that poly(ionic liquid)s with molecular weights less than 500 kDa showed a strong molecular weight dependency of their ionic conductivity . In conventional studies, most of poly(ionic liquid)s are prepared from ionic liquid monomers by radical polymerization . In such cases, the change in the ionic conductivity is attributable not only to the change in the chemical structure but also to the difference in the molecular weight.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…They confirmed that poly(ionic liquid)s with molecular weights less than 500 kDa showed a strong molecular weight dependency of their ionic conductivity . In conventional studies, most of poly(ionic liquid)s are prepared from ionic liquid monomers by radical polymerization . In such cases, the change in the ionic conductivity is attributable not only to the change in the chemical structure but also to the difference in the molecular weight.…”
Section: Introductionmentioning
confidence: 72%
“…To date, various types of poly(ionic liquid)s have been reported . Their reported ionic conductivity values range from 10 −8 to 10 −4 S cm −1 at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a common neutral polymer precursor with well-defined structural characteristics for the development of a series of PILs with different counter-anions permits to exclusively pinpoint the impact of the counteranion and to establish a precise structure-property relationship.Polyacrylate-based TPILs 29-32 having a triethylene glycol (TEG) spacer were then prepared using a parallel yet significantly different approach based on post-polymerization azidation and CuAAC reactions(Fig. 7b) 71. RAFT polymerization of chloride-functionalized acrylate 24 using trithiocarbonate 25 as chain transfer agent and V-70 as initiator afforded polyacrylate 26 (M n SEC = 24 kDa, Ð = 1.33, CHCl 3 , PS standards), the common neutral precursor of PT 28 and TPILs 29-32.…”
mentioning
confidence: 99%
“…Figure a shows the relationship between the σ DC value and reciprocal temperature for the cationic GTPs with the N ‐methyl substituent. The ionic conductivities of all cationic GTPs followed Vogel–Fulcher–Tammann (VFT) type temperature dependence, which reflects the coupling of the segmental motion of the polymer and the ion transport . The data were fitted with the following equationσDC=σ×exp(DσTσ/(TTσ))where σ ∞ is the ionic conductivity at T → ∞, D σ is the strength parameter related to the divergence from the Arrhenius temperature dependence, and T σ is the Vogel temperature at which the free volume extrapolates to zero.…”
Section: Resultsmentioning
confidence: 99%